KEWENANGAN BADAN KEHORMATAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM MENYELESAIKAN PELANGGARAN KODE ETIK YANG DILAKUKAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH - Tunu, Jefrian R; Stefanus, Kotan Y; Lamataro, Cyrilius W. T (Petitum Law Journal, 2023)
In Law no. 1 of 2015 Article 1 number 3. Members of the DPR are required to avoid inappropriate or improper behavior that could undermine the image and honor of the DPR both inside and outside the DPR building according to the ethics and norms that apply in society. This shows that a member of the DPR must be very careful in his words and actions, not only to maintain the honor and image of the DPR but also to reflect the representation of the people's representatives. a member of the TTS DPRD who violated the code of ethics which damaged the name and dignity of a TTS DPRD member because an individual member of the TTS DPRD committed an unlawful act in the case of an individual from the TTS DPRD with the initials JN committing sexual harassment against a victim. with the initials DLS, this matter was reported to the TTS DPRD Honorary Board for trial. The formulation of the problem in this research is: (1) What is the authority of the Honorary Body of the Regional People's Representative Council in resolving violations of the code of ethics committed by members of the Regional People's Representative Council? (2) How is the authority of the Honorary Council of the Regional People's Representative Council used in resolving violations of the code of ethics committed by members of the TTS Regional People's Representative Council? This research is normative legal research. Normative legal research is research carried out by examining library materials or secondary data. The results of this research show that: (1) The Honorary Board of the Regional People's Representative Council has the authority to prevent and take action against members of the Regional People's Representative Council who violate the code of ethics of the Regional People's Representative Council. (2) The Honorary Body of the Regional People's Representative Council of South Central Timor has not effectively used its authority in resolving violations of the code of ethics because it is shackled to the solidarity of members of the Regional People's Representative Council who have no experience in using the honorary body of the Regional People's Representative Council and are immersed in their respective activities.